"The greatest workers of the world"*: Philippine labor out-migration and the politics of labeling in Gloria Macapagal-Arroyo's presidential rhetoric. (1st September 2016) - Serquiña, Oscar Tantoco
Abstract: This paper initiates a critical analysis of the State of the Nation Addresses (SONA) and occasional speeches through which the presidency of Gloria Macapagal-Arroyo constructed figures of overseas Filipino workers (OFWs). First, it connects the former Philippine head of state's banner vision of a "Strong Republic" to labor out-migration. Second, it surveys the labels Macapagal-Arroyo tapped to refer to or categorize migrant workers. And finally, it problematizes the politics behind state labeling and its participation in migrant discourses within and beyond the Philippine nation. Results show that Arroyo hailed migrant workers as the country's "greatest export, " as its "investors, proprietors, stakeholders, and philanthropists, " and as its "full partners in developmental, demographic and democratic transformation." By calling OFWs names based on market economies, the former president tried to rhetorically transform migrant identities and subjectivities usually immersed in sacrifice, hardship, and pity into something more appealing for the "modern" and "global" status to which the Philippine nation-state aspires. In this light, rhetorical enterprises such as presidential speeches may be seen as a crucial communicative technology of a political institution that perpetrates practices of control toward its exported human labor, and that employs discursive apparatuses to manage labor exportation within the ambits of neoliberal globalization and state power.